Heat killed Saccharomyces cerevisiae as an adjuvant for the induction of vaccine-mediated immunity against infection with Mycobacterium tuberculosis. Issue 25 (27th May 2016) - Grover, Ajay; McLean, Jennifer L.; Troudt, JoLynn M.; Foster, Chad; Izzo, Linda; Creissen, Elisabeth; MacDonald, Elisabeth; Troy, Amber; Izzo, Angelo A.
Highlights: First studies to demonstrate the effective use of a Mycobacterium tuberculosis antigen expressing recombinant heat-killed yeast vaccine. The recombinant heat-killed yeast vaccine induced CD4 + and CD8 + T cell immunity. The recombinant heat-killed yeast can be used to boost BCG induced immunity. Abstract: The use of novel vaccine delivery systems allows for the manipulation of the adaptive immune systems through the use of molecular adjuvants that target specific innate pathways. Such strategies have been used extensively for vaccines against cancer and multiple pathogens such as Mycobacterium tuberculosis . In the current study we used heat killed non-pathogenic recombinant Saccharomyces cerevisiae expressing M. tuberculosis antigen Rv1886c (fbpB, mpt59, Ag85B) as a delivery system in conjunction with its ability to stimulate innate immunity to determine its ability to induce immunity. We established that the recombinant yeast induced activated antigen specific T cells are capable of reducing the mycobacterial burden. Inoculation of the recombinant yeast after vaccination with BCG resulted in a systemic alteration of the phenotype of the immune response although this was not reflected in an increase in the reduction of the mycobacterial burden. Taken together the data suggest that heat killed yeast can induce multiple cytokines required for induction of protective immunity and can function as a vehicle for delivery of M. tuberculosis antigens in a vaccine formulation. In addition, while it can enhance the effector memory response induced by BCG, it had little effect on central memory responses.